Factores biológicos y psicosociales, e intento de suicidio en Loja - Fierro Betancourth, Ana Katherine (2014)
This research descriptive, cross sectional, in order to: Identify the biological and psychosocial factors in the onset of depressive symptoms in patients poisoned by various substances with suicidal purposes; and Develop an information leaflet about the management of patients with attempted suicide, knowing its causes and complications to get proper guidance and treatment directed toward medical and paramedical staff of Isidro Ayora Hospital, through the application of an interview on the Hospital mentioned between the months of June and November 2013, 15 cases of acute poisoning with suicidal purposes were studied, observing that the male population was higher than the female by a ratio of 2:1 and that the main cause was heartbreak (67%), prioritizing psychosocial factors over biological, also, the persistence of depressive symptoms was evident after the emergency is over, so it is important to seek deeper into the origins of depression and fully treat the patient as far as possible to achieve reintegrate into society. Keywords: suicide attempt, depression, autolysis, biological and psychosocial factors.